CORPORATE CRIMINAL ACCOUNTABILITY IN FULFILLING THE RIGHT TO RESTITUTION OF VICTIMS OF PEOPLE TRAFFICKING - Thomas Petrus Gekeng Tukan; Tofik Yanuar Chandra; Kristiawanto; Yuhelson; Ramlani Lina Sinaulan (Scholar Express Journals, 2023)
So far, the role of corporations in human trafficking has been quite significant. So that there needs to be a study related to criminal responsibility in fulfilling the rights of victims of the Crime of Human Trafficking (TPPO). The background of this writing discusses the formulation of the related problem: How is corporate criminal responsibility in TIP? And how is corporate criminal responsibility in fulfilling the rights of restitution for victims of TIP? This article uses a normative juridical research method that examines various laws and regulations in Indonesia, then is analyzed descriptively. Regarding corporate criminal responsibility, there is still very little going on in Indonesia. Whereas in Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking, corporations have been accepted as subjects of criminal law on trafficking in persons who can be held criminally responsible. One of the responsibilities that must be fulfilled by corporations as criminal actors is the fulfillment of victims' rights of restitution
Keywords: accountability; criminal human trafficking; corporations; restitution